Politik Hukum Sistem Pemilihan Umum Presiden dan Wakil Presiden dalam Perspektif Pancasila - Taufiq, Adnan; Suhariyanto, Didik; Ismail, Ismail (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The research objectives in this thesis are based on the two problem formulations raised, namely as follows: To find out and study the Presidential and Vice Presidential Election system based on Law Number 7 of 2017 concerning General Elections. To find out and study the Legal Politics of the President and Vice President in Indonesia based on Law Number 7 of 2017 concerning General Elections, viewed from the Pancasila Perspective. The research method used is normative juridical legal research. The results of the research and discussion are as follows: First, the direct and indirect Presidential election system emerged due to a misinterpretation of the 4th principle of Pancasila which reads "the people are led by wisdom in deliberation/representation". Second, the legal politics of a statutory norm fall into the category of open legal policy, so according to the Constitutional Court this norm is in an area of constitutional value with the 1945 Constitution. The concept of open legal policy itself was first used by the Constitutional Court. In its considerations, the Constitutional Court was of the opinion that such a policy choice is the right of the legislator and is protected by the constitution.